EFFECT OF THE GEOMETRY AND MOORING LINE ON THE HYDRODYNAMICS OF A PONTOON MODEL FOR MARINE FLOATING PHOTOVOLTAICS: Renewable Energy Technology and Engineering (Journal of Energy and Safety Technology (JEST), 2025)
This study aimed to analyze the effects of different pontoon models, including variations in pontoon geometry and mooring lines, on the hydrodynamic responses of marine floating photovoltaic (FPV) systems using numerical models. The examined variables included the geometric shapes of the pontoons, the number of mooring lines, irregular wave patterns, and water depth. The results demonstrate that adding pontoons with breakwater geometries—specifically cylindrical and rectangular shapes—results in lower hydrodynamic responses than the Pure float model. Among the models tested, the breakwater configuration achieved the most significant reduction in hydrodynamic responses, with a decrease of 59% across the six degrees of freedom (DOF). The rectangular model was closely followed, with a 56% reduction, whereas the cylindrical model showed a 47% reduction. The use of six mooring lines can further minimize the effects of wave excitation and hydrodynamic responses across the six DOFs. On average, adding the mooring lines resulted in a 27% reduction in the response amplitude operator (RAO) values and a 9% decrease in the mooring line tension. This research provides valuable insights for designing and developing efficient and reliable marine FPVs, serving as a practical guide for the renewable energy industry to enhance performance and system sustainability.Keywords—Marine Floating Photovoltaic (Marine FPV), Breakwater Mooring Line, Response Amplitude Operator (RAO).
Keywords: Marine Floating Photovoltaic (Marine FPV), Breakwater Mooring Line, Response Amplitude Operator (RAO).